THE ACTIVISM AND SURVIVAL OF THE RIAU-LINGGA ‘ULAMA’ IN THE DUTCH EAST INDIES COLONIAL ERA (1900-1913) (JOURNAL OF INDONESIAN ISLAM, 2018)
The Riau-Lingga Sultanate, previously known as the Sultanate of Johore, covered a large region which included the Riau-Lingga islands, Singapore, some parts of Malaya and some parts of the Sumatera eastern coasts. It was considered a powerful Malay kingdom in the region. However, after the defeat of the Yang Dipertuan Muda Riau Raja Haji in 1784, which was followed by the one-sided Anglo-Dutch Treaty in 1824, the sultanate became divided, with only a small part of the region remaining under its rule. This paper attempts to explore the role of ‘ulama’ in Riau Lingga during the Dutch colonial politics in the region, especially in relation to the discussion of the development of Islam in the early twentieth century Indonesia. It discusses the role and contribution some of the most influential scholars and ‘Ulama’ in the sultanate included Raja Ali Tengku Kelana also known as Raja Ali Kelana, Raja Hitam or Raja Khalid Hitam, Raja Abdul Rahman Kecik, Raja Muhammad and the candidate for the Riau-Lingga sultan, Tengku Besar.